A transição para a democracia na Argentina (1984-1989): um balanço do governo Alfonsin - Ayerbe, Luis Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 1991)
Neste artigo, pretendemos mostrar como a transição para a democracia na Argentina, apesar dos sinais de maior estabilidade institucional, convive com a consolidação de um econômico-social cujos sinais de crise tendem a acentuar cada vez mais o seu caráter excludente.

This paper tries to show how the transition to democracy in Argentine, inspite the indications of institutional instability, occurs together the consolidation of a social-economic system of which the signs of the crises tend to emphasize more and more its excludent character.
The transition to democracy in Argentine (1984-1989): an analyses of the Alfonsin's government
Keywords: Democracia; crise econômica; pacto social; governabilidade